THE MECHANICAL BEHAVIOR OF SOFT MARINE CLAY STABILIZED WITH RECYCLED TILE MATERIAL - AL-BARED, MOHAMMED ALI MOHAMMED (2020)
This research aimed at determining the stabilization mechanisms and performance of marine clay mixed with recycled tile (RT) alone, RT-cement, and RT-lime